Literature Review: Aplikasi Mobile Fun Easy Learn Arabic dalam Pembelajaran Kosakata Bahasa Arab - Nur Fadila, Hani; Koderi, Koderi; Sodiq, Ahmad; Sagala, Rumadani (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
The learning of Arabic plays a crucial role in various fields such as religion, academics, business, and tourism. To achieve comprehensive mastery of the Arabic language, vocabulary enrichment (mufradat) serves as a fundamental basis. However, this learning process often faces challenges, particularly in the aspect of vocabulary acquisition. This study aims to analyze the features of the Fun Easy Learn Arabic application, evaluate its impact on Arabic vocabulary learning, and identify its strengths and limitations. The method employed is a literature review with a qualitative approach. Data were collected through documentation methods and analyzed using content analysis. The Fun Easy Learn Arabic application integrates modern technology with educational game-based learning methods to enhance Arabic language skills. It combines visual, audio, and kinesthetic elements into a comprehensive multisensory approach. Features such as flashcards, interactive quizzes, and educational games facilitate enjoyable and structured learning processes, improving memory retention through principles of spaced repetition and dual coding. Overall, the Fun Easy Learn Arabic application can serve as an effective learning medium to enhance Arabic vocabulary acquisition, especially when used as a complement to broader learning methods. The integration of technology in foreign language learning offers significant potential to boost students' motivation and learning outcomes